Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.hrtlng.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of patient characteristics, psychologic status, and cognitive function as predictors of self-care in persons with chronic heart failure

Abstract: Although cognitive function added to the model in predicting both self-care maintenance and management, it was not a significant predictor of CHF self-care compared with other modifiable and nonmodifiable factors. Depression explained only self-care management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 49 publications
5
129
1
Order By: Relevance
“…Eleven of the articles were rated as good quality, fifteen as fair quality (the articles are numbered according to quality score in Tables 2 and 4; studies numbered 1-11 are rated as good quality [18][19][20][21][22][23][24][25][26][27][28], and those numbered 12-26 are rated as fair quality [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]). Four articles were excluded due to a low quality score [44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the articles were rated as good quality, fifteen as fair quality (the articles are numbered according to quality score in Tables 2 and 4; studies numbered 1-11 are rated as good quality [18][19][20][21][22][23][24][25][26][27][28], and those numbered 12-26 are rated as fair quality [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]). Four articles were excluded due to a low quality score [44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies used the term ''self-care'' [26,27,33,40,43], other studies used other terms, including ''self-management'' [18,32,39], ''adherence'' [35], ''compliance'' [20,29,36] and ''self-care specific behaviours'' [21]. In addition, eight articles reported results on self-care management [22,25,30,31,33,38,41,42] and ten on self-care maintenance [22,25,30,31,33,34,37,38,41,42]. …”
Section: Resultsmentioning
confidence: 99%
“…11 Similarly, several recent studies have reported no independent effect of social support on HF self-care, regardless of the way social support was measured; for instance, as perceived emotional support 12 or marital status. 13,14 Ultimately, only one published study was found that linked social support and HF patients' self-care, in this case indicating that lack of social support, as measured by not having a partner, was associated with worse self-care overall. 15 Together these results suggest that there is a need to differentiate the effect of having a partner from the level of support the partner provides.…”
Section: Introductionmentioning
confidence: 89%
“…medical management adherence, smoking cessation, physical activity, diet), there remain a number of questions about specific content and how to deliver self-management support in general, and for CHF in particular [18]. For clinicians, a consistent area of concern is the desire among patients for improved care, which is consistent with the findings from previous investigations stating that quality of communication and duration of the relationship between physician and patient affect the health literacy and self-efficacy of patients.…”
Section: Resultsmentioning
confidence: 99%